Effect of Dietary Raw Chick Pea (Cicer arietinum L.) Seeds on Broiler Performance and Blood Constituents - Algam, Tamador. A.; Atti, Khadiga. A. Abdel; Dousa , B.M.; Elawad, S.M.; Elseed, A.M. Fadel (International Journal of Poultry Science, 2012)
One hundred and twenty eight broiler chicks were used to evaluate the effect of dietary level chickpea seeds, on performance and some blood parameters of broilers. Four iso caloric and iso nitrogenous Experimental diets containing 0%, 5%, 10% and 15% raw chickpea seeds were formulated to meet the nutrients requirements as outlined by NRC (1994). Experiment was in a Completely Randomize (CRD) comprised broiler chick diet. Each treatment was replicated four times with 8 birds/replicate. The study lasted for 45 days. Parameters measured were feed intake, body weight gain, Feed Conversion Ratio (FCR), pre-slaughter weight, dressing percentage, protein efficiency, some blood parameters (glucose, cholesterol, triglyceride, total protein, calcium and phosphorus) and profitability. Results revealed that treatment had no significant effect in feed intake and blood serum parameters. Birds fed 10% and 15% of chickpea showed similar performance to control significant (p<0.05) on body weight gain Feed Conversion Ratio (FCR), pre-slaughter weight, dressing percentage, protein efficiency, However, birds fed on 5% level is significantly (p<0.05) lower on weight gain, carcass weight and Feed Conversion Ratio (FCR), bird fed 10%level chickpea has better effect on net profit.